![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1. 2x=16\(\Rightarrow\)X=4
2. 22x-1=27
\(\Rightarrow\)27=22.4-1
Vậy x =4
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a)\)\(\left(50-6.x\right).18=2^3.3^2.5\)
\(\Leftrightarrow\)\(\left(50-6.x\right).18=8.9.5\)
\(\Leftrightarrow\)\(\left(50-6.x\right).18=360\)
\(\Leftrightarrow\)\(\left(50-6.x\right)=360\div18\)
\(\Leftrightarrow\)\(50-6.x=20\)
\(\Leftrightarrow\)\(6.x=50-20\)
\(\Leftrightarrow\)\(6.x=30\)
\(\Leftrightarrow\)\(x=5\)
\(b)\)\(\left(x+1\right)+\left(x+2\right)+\left(x+3\right)+...+\left(x+100\right)=7450\)
\(\Leftrightarrow\)\(100x+\left(1+2+3+...+100\right)=7450\)
\(\Leftrightarrow\)\(100x+5050=7450\)
\(\Leftrightarrow\)\(100x=7450-5050\)
\(\Leftrightarrow\)\(100x=2400\)
\(\Leftrightarrow\)\(x=24\)
b.
(x+1)+(x+2)+...+(x+100)=7450
=> 100x + (1+2+3+...+100)=7450
=>100x + (100+1).50=7450
=>100x=2400
=>x=24
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\left(-5\right).\left|x\right|=-75\)
\(\left|x\right|=\frac{-75}{-5}=15\)
\(\Rightarrow\orbr{\begin{cases}x=15\\x=-15\end{cases}}\)
Vậy....
\(b,\left(-6\right)^3.x^2=-1944\)
\(-216.x^2=-1944\)
\(x^2=9\)
\(\Rightarrow x=\pm3\)
Vậy....
\(d,\left|9-x\right|=-7+64\)
\(\left|9-x\right|=57\)
\(\Rightarrow\orbr{\begin{cases}9-x=57\\9-x=-57\end{cases}\Rightarrow\orbr{\begin{cases}x=-48\\x=66\end{cases}}}\)
Vậy...
\(e,\left|x+101\right|-\left(-16\right)=\left(-43\right).\left(-5\right)\)
\(\left|x+101\right|+16=215\)
\(\left|x+101\right|=199\)
\(\Rightarrow\orbr{\begin{cases}x+101=199\\x+101=-199\end{cases}\Rightarrow\orbr{\begin{cases}x=98\\x=-300\end{cases}}}\)
Vậy..
hok tốt!!
a,\(\left(-5\right).\left|x\right|=-75\)
\(=>\left|x\right|=-75:\left(-5\right)=15\)
\(=>\orbr{\begin{cases}x=15\\x=-15\end{cases}}\)
b,\(\left(-6\right)^3.x^2=-1944\)
\(=>\frac{1944}{216}=x^2\)
\(=>x=\sqrt{\frac{1944}{216}}=3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
2(x-1)-12=36
2(x-1)=36+12
2(x-1)=48
x-1=48/2
x-1=24
x=24+1
x=25
vậy x = 25
x-7=(-13)+(-8)
x-7=-21
x=-21+7
x=-14
vậy x=-14
(-43) + 158 + 33 + (-158) +17
=\([(-158)+158]\)\((33+17)-43\)
=50-43
=7
![](https://rs.olm.vn/images/avt/0.png?1311)
a,5mũ 36=(5mũ3)mũ12=125 mũ12
11^24=(11^2)12=121^12
vì 121<125 nên 5^36>11^24
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2840 + [(999 - 9x) : 60 ] .24 = 3200
=> [(999-9x) : 60 ] . 24 = 2840 - 3200 = -360
=> (999 - 9x) = \(\frac{-360}{24}=-15\)
=> 9x = 999 - ( - 15) = 999 + 15 = 1014
=> x = \(\frac{1014}{9}=\frac{338}{3}\)
b) (3x - 48) . 6 = 33.22 - 23.32
(3x - 48) . 6 = 27 . 4 - 8 . 9
(3x -48).6 = 36
(3x - 48 = 36 : 6 = 6
3x = 54
x = 54 : 3 =18
t ick cho mik nha
\(\left(x+1\right)^2=36=\left(\pm6\right)^2\)
\(\Rightarrow\orbr{\begin{cases}x+1=6\\x+1=-6\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=5\\x=-7\end{cases}}\)
Vậy x = { -7; 5 }
(x+1)2 = 36 = 62 = (-6)2
=> x + 1 = 6 => x = 5
x+1 = -6 => x = -7
KL:...